Impact of Nursing Clinical Learning During the COVID-19 Pandemic - Suryadi Suryadi; Andi Masyitha Irwan; Takdir Tahir (Jurnal Keperawatan Silampari, 2023)
This research aims to determine the impact of clinical nursing learning during the COVID-19 pandemic. The research method used in this research is literature review research using source search articles in the PubMed database with inclusion criteria from 2020 to 2022 and providing full text. The keywords used were "nursing education," "pandemic," "nursing challenges," and "university during the pandemic." The research results showed eight articles regarding the impact of learning clinical nursing experiences through virtual learning, support for self-efficacy became stronger, satisfaction with learning aspects of clinical nursing _ and medical surgery, and students' spiritual practice became more muscular. In conclusion, this virtual learning also has many positive aspects, including providing new experiences in nursing practice and allowing students to adapt to conditions in different environments. Keywords: COVID-19, Impact, Nursing, Learning Clinic, Virtual